Dual-source CT Angiography in Aortic Stent Grafting: An in vitro Aorta Phantom Study of Image Noise and Radiation Dose - Sun, Zhonghua; Ng, Curtise (Elsevier Ltd, 2010)
Rationale and Objectives: The aim of the study was to investigate the optimal protocols of dual-source computed tomography (CT) angiographyin aortic stent grafting in terms of image noise and radiation dose, based on an in vitro phantom study. Materials and Methods: A series of helical CT cans were performed on a human aorta phantom using a dual-source CT scannerwith kVp of 100, 120, and 140, corresponding mAs of 180, 150, and 100; slice thickness of 1.0, 1.5, and 2.0 mm; and pitch value of 0.5, 1.0, and 1.5, respectively. Image quality was determined by measuring the standard deviation (SD) on three-dimensional virtual intravascular endoscopy (VIE) images. Signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR) were measured on two dimensional(2D) axial images at superior mesenteric artery (SMA), renal arteries, and aneurysm. Effective dose was determined based on dose-length product.Results: SD measured on VIE images was independent of kVp and pitch values but was determined by the slice thickness (P <.05) at the SMA and renal arteries. SNR and CNR measured on 2D images showed significant differences between variable kVp values and slice thicknesses (P <.05), but were independent of pitch values. The mean estimated effective dose for 120 kVp and 140 kVp protocols were 2.66 ± 0.21 mSv and 2.68 ± 0.18 mSv, respectively. The mean estimated effective dose for 100 kVp protocol was significantly lower (1.97 ± 0.07 mSv, P < .0001). This indicates a reduction of 26.5% radiation dose when the kVp was lowered from 140 to 100. Conclusion: A scanning protocol of 1.5-mm slice thickness, pitch 1.5 with 100 kVp, and 180 mAs is recommended for a dual-source CT angiography in aortic stent grafting as it leads to significant reduction of radiation dose while achieving diagnostic images.